MENGATASI PERMASALAHAN USAHA KULINER TRADISIONAL DI INDONESIA - Antasalam Ajo (Media Agribisnis, 2020)
Abstract Indonesia's traditional culinary business has not reached the scale that provides prosperity for small entrepreneurs. The purpose of the study is to obtain a solution format or traditional culinary business development program to build traditional Indonesian cuisine. This research is qualitative research by collecting previous research documents assisted by ATLAS. ti software version 8. The research found internal culinary business problems such as price, service, and hygiene of products, location, resources, interests, motivation, and entrepreneurial mentality, utilization of social media, traditional management, tools, access to funds, technology, infrastructure, and market reach, and do not yet have halal certificates. Meanwhile, external problems such as an unstable economy are exacerbated by the COVID-19 pandemic, global competition, preference for fast food, and competition with new entrepreneurs. Solutions or programs offered include training programs, increased added value, product variation, packaging innovation, service quality, promotion, positive interaction with consumers, and product satisfaction guarantees. Further, the courage to take risks, self-awareness in the face of change, as well as be grateful for all the favors. The government needs capital assistance, a supportive climate, good partnerships, protection, training, promotion, and equal cooperation, strengthening the creative economy, and improving community empowerment programs for example through integration with tourism. Keywords: Problems, culinary, development program